PENGARUH PELATIHAN KERJA, KUALITAS KEHIDUPAN KERJA, DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA (Studi Pada Pegawai Kelurahan Petukangan Utara): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur Jakarta - ., Amalia; Wahyudi, Widi (PT. Media Edutama Nusantara, 2024)
This study employs a quantitative approach to examine the relationship between job training, quality of work life, and work experience with work productivity among employees of the North Petukangan sub-district. A total of 37 employees participated in this research by completing an online questionnaire. Data analysis was conducted using simple and multiple linear regression with IBM SPSS 22 software. The findings of this study highlight the crucial role of work experience in enhancing employee productivity. Unlike job training and quality of work life, work experience has been proven to be a significant determinant in improving employee productivity.